The effect of design thinking approach in interprofessional education programme of human sexuality course: A quasi‐experimental design - Cheng‐Yi Huang; Li‐Ya Tsai; Chu‐Hua Chung; Fen‐Fen Shih; Yu‐Ming Wang (Wiley, 2023)
Abstract Aims To determine the effect of design thinking approach in interprofessional education programme of human sexuality course. Design A pre‐test and post‐test of single‐group quasi‐experimental study. Methods The 35 nursing students and seven psychology students in their third year were selected by the computer randomly sampling through the lottery method. The course proceeded between September 2019 and January 2020. The participants had received an 8‐week, 16‐hr design thinking approach in interprofessional education programme of human sexuality course (one section per week, 2 hr per section). We used the nursing attitude toward sexual healthcare scale, nursing intervention toward sexual healthcare scale to assess students' attitude and behaviour intention toward sexual health care and competence of interprofessional education scale to assess students' competence of cooperation before and after the teaching programme. Data analysis used descriptive statistics and t‐tests. A qualitative reflection log was also provided and analysed for themes. The SQUIRE‐EDU checklist was followed. Results The students' attitude and behavioural intention dimension score in the post‐test is higher than those in the pre‐test and reach statistically significant differences both in total and subscale. Interprofessional core competence score of Observation Experience, Reflective Feedback, Interprofessional Cooperation, Innovative Design, and Applied Technology score in the post‐test is higher than those in the pre‐test and reach statistically significant differences both in total and subscale. Design thinking in interprofessional education programme of human sexuality course could significantly improve both nursing and psychology students' attitude, behaviour intention of providing sexual health care and competence of interprofessional cooperation.